Divergent Effects of Hypertonic Fluid Resuscitation on Renal Pathophysiological and Structural Parameters in Rat Model of Lower Body Ischemia/Reperfusion-Induced Sterile Inflammation. Issue 6 (December 2018) - Ergin, Bulent; Zuurbier, Coert J.; Kapucu, Aysegul; Ince, Can
Abstract : ABSTRACT: The pathogenesis of acute kidney injury (AKI) is characterized by the deterioration of tissue perfusion and oxygenation and enhanced inflammation. The purpose of this study was to investigate whether or not the hemodynamic and inflammatory effects of hypertonic saline (HS) protect the kidney by promoting renal microcirculatory oxygenation and possible deleterious effects of HS due to its high sodium content on renal functional and structural injury following ischemia/reperfusion. Mechanically ventilated and anesthetized rats were randomly divided into four groups (n = 6 per group): a sham-operated control group; a group subjected to renal ischemia for 45 min by supra-aortic occlusion followed by 2 h of reperfusion (I/R); and I/R group treated with a continuous i.v. infusion (5 mL/kg/h) of either % 0.9 NaCl (IR+NS) or %10 NaCl (I/R+HS) after releasing the clamp. Systemic and renal hemodynamic, renal cortical (CμPO2 ), and medullar microcirculatory pO2 (MμPO2 ) are measured by the oxygen-dependent quenching of the phosphorescence lifetime technique. Renal functional, inflammatory, and tissues damage parameters were also assessed. HS, but not NS, treatment restored I/R-induced reduced mean arterial pressure, CμPO2, renal oxygen deliver (DO2ren ), and consumption (VO2ren ). HS caused a decrease in tubular sodium reabsorption (TNa + ) that correlated with an elevation of fractional sodium excretion (EFNa + ) and urine output. HS had an anti-inflammatory effect by reducing the levels TNF-α, IL-6, and hyaluronic acid in the renal tissue samples as compared with the I/R and I/R+NS groups ( P < 0.05). HS treatment was also associated with mild acidosis and an increased renal tubular damage. Despite HS resuscitation improving the systemic hemodynamics, microcirculatory oxygenation, and renal oxygen consumption as well as inflammation, it should be limited or strictly controlled for long-term use because of provoking widespread renal structural damage.